Foreign language reading anxiety in a Jordanian EFL context: a qualitative study - Al-Shboul, Murad M.; Sheikh Ahmad, Ismail; Nordin, Mohamad Sahari; Abdul Rahman, Zainurin (Canadian Centre for Science and Education, 2013)
In the last two decades, investigating the sources of foreign language anxiety in general has increasingly attracted the attention of many researchers in the field of foreign language teaching. However, the sources of anxiety that influence the acquisition of certain specific language skills such as reading in particular have rarely been investigated. Thus, the aim of this study was to explore and understand the underlying problems and factors that contribute to reading anxiety faced by EFL students at Yarmouk University, Jordan. It was a qualitative exploration of the sources of English language reading anxiety for which observation, semi-structured interviews and diaries were collected from six informants with different levels of English language proficiency. The findings of the study revealed that there were two aspects of foreign language reading anxiety: personal factor and text feature. Under the concept of personal factor there were also two main sources of foreign language reading anxiety, which are: afraid of making errors and worry about reading effects. On the other hand, there were three main sources of foreign language reading anxiety under the concept of text feature, which are: unknown vocabulary, unfamiliar topic, and unfamiliar culture. The five main sources of foreign language reading anxiety were arranged according to their occurrences and percentages in the study. Moreover, recommendations were proposed.